2005
DOI: 10.1093/annonc/mdi908
|View full text |Cite
|
Sign up to set email alerts
|

Specific TP53 and/or Ki-ras mutations as independent predictors of clinical outcome in sporadic colorectal adenocarcinomas: results of a 5-year Gruppo Oncologico dell'Italia Meridionale (GOIM) prospective study

Abstract: Specific TP53 mutations in L3 domain alone (only in DFS) or in combination with specific Ki-ras mutations at codon 13 are associated with a worse prognosis in sporadic CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 25 publications
8
48
0
3
Order By: Relevance
“…A previous report looking at exchange kinetics for G13D HRAS using NMR also found a similar approximately 15-fold increase in nucleotide exchange rate for G13D compared with WT HRAS, indicating that SOS-independent auto-activation may be a general phenomenon for all G13D mutants of RAS-family members (58). The relatively fast exchange kinetics measured for the G13D mutant could contribute to the more aggressive biology of G13D-associated tumors seen in some studies (59), although there are also contexts in which G13D-associated tumors interact favorably with specific treatment regimens (26). We also note that the fast exchange kinetics of G13D may provide more access to the active site for small-molecule inhibitors if compounds with sufficient binding affinity can be developed.…”
Section: Discussionsupporting
confidence: 55%
“…A previous report looking at exchange kinetics for G13D HRAS using NMR also found a similar approximately 15-fold increase in nucleotide exchange rate for G13D compared with WT HRAS, indicating that SOS-independent auto-activation may be a general phenomenon for all G13D mutants of RAS-family members (58). The relatively fast exchange kinetics measured for the G13D mutant could contribute to the more aggressive biology of G13D-associated tumors seen in some studies (59), although there are also contexts in which G13D-associated tumors interact favorably with specific treatment regimens (26). We also note that the fast exchange kinetics of G13D may provide more access to the active site for small-molecule inhibitors if compounds with sufficient binding affinity can be developed.…”
Section: Discussionsupporting
confidence: 55%
“…The prognostic value of K-Ras mutations has been demonstrated in case-control studies (Bazan et al, 2005;Conlin et al, 2005;Poehlmann et al, 2007). In our study, although the association between K-Ras mutation status and EFS was limited to stage I-III, we found that mutations at codon 12 of K-Ras were significantly associated with poorer EFS in all stages.…”
Section: Discussionsupporting
confidence: 38%
“…Associations with 12 codon present mucinous type cancer mutations, while mutations in codon 13 are related to non-mucinous cancer, however this type is more aggressive with higher metastatic rate. [16][17][18] A KRAS mutation can be considered as bad prognosis mainly in the codon 13, and is also considered to be a biomarker that predicts the response to therapy through EGFR. 17 The genetic mechanism begins with an inactive mutation of the tumor suppressor gene APC, which is responsible for familial adenomatous polyposis, and approximately 85% of colorectal cancer without hereditary relationship.…”
Section: Epidemiologymentioning
confidence: 99%